An open chat with…Pierre Santucci: a testimonial on why we should engage with scientific societies and their journals - Pierre Santucci; Ioannis Tsagakis (FEBS Open Bio)
Scientific societies constitute a cornerstone in our scientific landscape by supporting research activities, fostering networking opportunities and promoting extensive training and education in basic sciences. As membership‐based organisations, scientific societies provide their members with access to meetings, workshops, educational programs and also funding opportunities through fellowships and awards. Societies also run and supervise the publishing activities of their sponsored journals that benefit authors and the entire community by enabling the publication of high‐quality studies by scientists, for scientists. Most societies or not‐for‐profit publishing organisations financially lean on memberships and their journals to support their activities. Therefore, engaging with and advocating for scientific societies and not‐for‐profit journals is important to help sustain their impactful activities and to raise awareness for fellow unaware scientists. In this piece, we discuss with our newly appointed Publishing Liaison Officer, Pierre Santucci, how scientific societies and sponsored journals can have a direct and beneficial impact on a scientist's career. Pierre also provides a short testimonial of his experience with FEBS initiatives and FEBS Press journals.